Postcard of Jean Piaget - Piaget, Jean, 1896-1980.
Signed postcard (1942 September 18) written by Piaget to R. Bassalier thanking him for the proofs of The Intellectual Development of Children (undated).
Psychologist and author.
Collection material in French.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Bassalier, R. -- Correspondence; Psychologists; Authors